Death toll among the Bangladeshi refugees of the 1971 war - Kaustubh Adhikari; Nazmul Islam; Mohammad Mahbubur Rahman Jalal (PLoS ONE, 2025)
Bangladesh achieved its independence in 1971 through a violent liberation war. To avoid persecution by the Pakistani army, 9.9 million Bangladeshi refugees escaped to India. Medicine and food supplies to these camps were not adequate to meet the necessities of such a large population of refugees. Therefore, poor condition of these camps resulted in a higher death rate among the refugees than the peacetime death rate of Bangladeshis. This paper reviews reported death tolls in several refugee camps in India as published in newspapers and peer-reviewed journals. Extrapolating these figures, we estimate the total death toll among the refugees in 1971. We also estimate the overall ‘excess death toll’, the difference between the actual death toll and the expected natural death toll among these refugees, to be approximately 562,915 deaths. The confidence interval for the estimated excess death toll among the refugees is (323,562, 802,268) deaths.